2017
DOI: 10.1002/ajmg.a.38465
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions to improve cognition and adaptive functioning in Down syndrome: Strides to date

Abstract: Although an increasing number of clinical trials have been developed for cognition in Down syndrome, there has been limited success to date in identifying effective interventions. This review describes the progression from pre-clinical studies with mouse models to human clinical trials research using pharmacological interventions to improve cognition and adaptive functioning in Down syndrome. We also provide considerations for investigators when conducting human clinical trials and describe strategies for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 101 publications
0
35
0
Order By: Relevance
“…In the case of FXS, more than two dozen clinical trials testing a range of promising drugs have largely failed to show efficacy in humans [11]. Failed trials have been the norm for other ID conditions as well [18]. The lack of appropriate outcome measures for individuals with FXS and other ID conditions has been viewed as one of the most important contributors to the failure of these trials [7,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of FXS, more than two dozen clinical trials testing a range of promising drugs have largely failed to show efficacy in humans [11]. Failed trials have been the norm for other ID conditions as well [18]. The lack of appropriate outcome measures for individuals with FXS and other ID conditions has been viewed as one of the most important contributors to the failure of these trials [7,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, previous studies in mouse models of Alzheimer's disease showed that JZL184 produces anti-inflammatory effects which may be obtained through a CB1R-independent mechanism (Chen et al, 2012;Piro et al, 2012). Although several compounds have improved memory deficits in Down syndrome mouse models, most of them have produced marginally positive results in clinical trials (Hart et al, 2017). We took several considerations to maximize the translational potential of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Testing of potential treatments in Ts65Dn mice has yielded an embarrassment of riches with more than a dozen pharmaceuticals or nutriceuticals reporting promising effects ( Fernandez and Reeves, 2015 ). For example, the recent clinical trial by Roche of the GABA-α5 antagonist RG1662 gave serious weight to experiments in mouse models showing that normalization of the balance of inhibitory and excitatory inputs to hippocampus could improve several hippocampal-based behavioral paradigms as well as long term potentiation (LTP), all of which are impaired in Ts65Dn and other DS models ( Braudeau et al, 2011 ; Siarey et al, 1997 ; Kleschevnikov et al, 2004 ; Hart et al, 2017 ). Improvements with RG1662 are dramatic in mice, but the human trial was terminated in Phase IIa due to lack of efficacy in a long term treatment paradigm ( https://clinicaltrials.gov/ct2/show/NCT02024789 ).…”
Section: Introductionmentioning
confidence: 99%